A Blanket Against Darkness - Harton, Catherine, 1983- (Literary translation (Ottawa, Ont.), 2019)
n these Nordic woods where forbearers call blowing snow the sweet breath of death, a jeweller uses bird feathers to create works of art, a 54-year old man corresponds with the author of a message in a bottle thrown out to sea, another awaits the onslaught of the storm to open wide his mouth and drink it whole. Nature opens its gills, in this book, where forgiveness is both sought after and offered. A Blanket Against Darkness is filled with talismans from the Earth. Its relic-filled landscapes, where one single movement can set off the migration of an entire colony, are constant reminders that one is never completely alone. Published by Marchand de feuilles in 2015, Traite des peaux was shortlisted for the Governor General's Literary Awards and for the Prix des Cinq continents de la Francophonie.